NMDA receptor deletion on dopamine neurons disrupts visual discrimination and reversal learning. (23rd April 2019) - Radke, Anna K.; Zweifel, Larry S.; Holmes, Andrew
Graphical abstract: Highlights: NMDARs on DAT + neurons were genetically deleted in mice. Mice were tested in a pairwise discrimination and reversal learning paradigm. DAT-NR1 null mutants were impaired at discrimination compared to controls. Mutants performed better than controls during late reversal (performance ≥50%). These data add to evidence that DA is involved in a range of reward-related behaviors. Abstract: The dopamine (DA) system is critical for various forms of learning about salient environmental stimuli. Prior work has shown that deletion of the obligatory NR1 subunit of the N -methyl-D -aspartate (NMDA) receptor on neurons expressing the DA transporter (DAT) in mice results in reduced phasic release from DA-containing neurons. To further investigate the contribution of phasic DA release to reward-related learning and cognitive flexibility, the current study evaluated DAT-NR1 null mutant mice in a touchscreen-based pairwise visual discrimination and reversal learning paradigm. Results showed that these mutants were slower to attain a high level of choice accuracy on the discrimination task, but showed improved late reversal performance on sessions where correct choice was above chance. A number of possible interpretations are offered for this pattern of effects, including the opposing possibilities that discrimination memory was either stronger by the completion of training (overtraining effect) or weaker (learning deficit), both of which could potentially produce faster reversal. These data add to the extensive literature ascribing a critical role for DAergic neurotransmission in cognitive functions and the regulation of reward-related behaviors of relevance to addictions.